Health Effects of Labor Market Policies: Evidence from Drug Prescriptions - Marco Caliendo (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Comprehensive evidence has shown that unemployment can have adverse effects on an individuals' mental and physical health condition. However little is known about the side effects of governmental policies that aim to promote the unemployed's reintegration into the labor market on the health status of participants. On the one hand, these interventions could have positive health effects if they increase the chances of finding new employment, however, on the other hand, they might also have unintended consequences as participation per se might be stressful. We analyze the consequences of two policies: 1) training programs that represent a group of supportive measures (carrots) and 2) sanctions as a very restrictive intervention (sticks) for on an in ow sample into unemployment in 2006/2007 and utilize a combination of Swedish administrative data on labor market and prescription drug records. We apply a dynamic difference-in-difference approach accounting for detailed information on socio-demographics, employment biographies and the individual prescription drug history to estimate the impact on three common types of health problems that can be assumed to show up and to be diagnosed quickly after a potential intervention: cardiovascular problems, mental health issues and infections. Our results show positive health effects for training programs, but no effect for sanctions.
Keywords: J68; I12; I18; H51; 330; Unemployment; Active labor market policy; Health Effects